A Time to kill - Grisham, John (London Arrow Books, 1996)
Carl Lee Hailey guns down the hoodlums who have raped his ten-year-old child. When the people outside of Clanton hear that a black man has killed two whites, the town is filled with an angry mob. Jake Brigance, the young lawyer appointed to defend Hailey, will do anything to protect his client.
Keywords: American fiction -- 20th Century -- American Fiction